Internal challenge to clinical trial project management: strategies for managing investigator compliance. Issue 3 (27th August 2013) - Cao, Hongbo; Shang, Hongcai; Mu, Wei; Zhai, Jinbo; Hou, Yazhu; Wang, Hui
Abstract Background Managing compliance in a clinical research, especially in a multi‐centre randomized clinical trial (MRCT) is vital. We now feel the need to take a look at the once overlooked area of investigator compliance as it may provide resources necessary for producing satisfactory trial outcomes. Objectives To analyze investigator performance and examine their adherence behavior using data collected and information gained from the MISPS‐TCM, a Chinese national research project. Methods Four researchers were responsible for collecting relevant information and investigating the compliance behavior of participants in MISPS‐TCM. The Data Management Committee of MISPS‐TCM offered us the number of withdrawal at each site and other site information. Reports on investigator compliance events were provided by the Monitoring Committee. Records of any misconduct of or errors made by the investigator were collected from the Center's daily management diary. Other information sources included trial managers and investigators at the Center or at different sites of the study. Results Investigator compliance can be an important determinant of trial outcomes and the degree of compliance may have detrimental effects on the reliability of findings of an MRCT, directly or indirectly. Conclusions Trial managers of future MRCTs should take a firm grip on investigator compliance from the following aspects. First, physicians should be provided with more opportunities. Second, we created and recommended the 'Five Step Method' for evaluating investigators. Third, measures must be taken to secure investigator compliance. Fourth, evaluation of investigator compliance in an MRCT needs to be made.